Video scene change detection based on histogram analysis for hiding message - M., Fuad; Ernawan, Ferda; Hui, L. J. (IOP Publishing, 2021)
The rapid growth of internet technology has greatly increased the opportunity for secrecy communication. Most of communications implemented compression method in digital applications due to fast transferring data in the limited bandwidth. In addition, the information can be changed by a third party in communication. This paper proposed a new hiding technique by modifying DCT coefficients in the video frames. The scene changes of the video data are identified based on histogram analysis for hiding locations. Scene changes among video frames are detected by measuring the significant difference of histogram analysis. The proposed hiding technique in video is also evaluated against MPEG-4 compression. The experimental results show that the proposed scheme achieved high imperceptibility with minimum visual distortion on the video quality. The proposed hiding scheme also can recover the concealed data from the compressed video. The results show that the extracted hidden message is able to resistant against MPEG compression.